1990
DOI: 10.1126/science.2110383
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Polymeric Immunoglobulin Receptor Required for Its Efficient Transcytosis

Abstract: The endosomal compartment of polarized epithelial cells is a major crossroads for membrane traffic. Proteins entering this compartment from the cell surface are sorted for transport to one of several destinations: recycling to the original cell surface, targeting to lysosomes for degradation, or transcytosis to the opposite surface. The polymeric immunoglobulin receptor (pIgR), which is normally transcytosed from the basolateral to the apical surface, was used as a model to dissect the signals that mediate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 258 publications
(167 citation statements)
references
References 37 publications
6
160
0
1
Order By: Relevance
“…Since it has been shown that phosphorylation at serine 664 of the pIgR or at serine 24 of the transferrin receptor plays no role for correct basolateral delivery (Casanova et al, 1990;Dargemont et al, 1993), it seems reasonable that the kinases phosphorylating the different sites and the subcellular location of interaction with the MPR46 are important. Both serine 726 of the pIgR as well as serine 56 of MPR46 are part of a consensus sequence of CK-2, whereas serine 664 of the pIgR and serine 24 of the transferrin receptor are located in protein kinase A and C consensus sequences, respectively (Kennelly and Krebs, 1991).…”
Section: Expression Of Mpr46 Mutants In Mpr-deficient Mouse Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it has been shown that phosphorylation at serine 664 of the pIgR or at serine 24 of the transferrin receptor plays no role for correct basolateral delivery (Casanova et al, 1990;Dargemont et al, 1993), it seems reasonable that the kinases phosphorylating the different sites and the subcellular location of interaction with the MPR46 are important. Both serine 726 of the pIgR as well as serine 56 of MPR46 are part of a consensus sequence of CK-2, whereas serine 664 of the pIgR and serine 24 of the transferrin receptor are located in protein kinase A and C consensus sequences, respectively (Kennelly and Krebs, 1991).…”
Section: Expression Of Mpr46 Mutants In Mpr-deficient Mouse Fibroblastsmentioning
confidence: 99%
“…Two tyrosine-based signals (Y688 and Y734) and the phosphorylation of serine 726 regulate the internalization of pIgR (Okamoto et al, 1992(Okamoto et al, , 1994. Finally, phosphorylation of serine 664 stimulates in the absence of receptor ligands the transcytosis of pIgR (Casanova et al, 1990;Hirt et al, 1993) by inactivation of the basolateral-sorting signal.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting cDNA was ligated into the BglII site of pCB6 (36) and transfected into MDCK strain II cells as described previously (4). Mutants in which serine 664 has been mutated to alanine (S664A) or aspartic acid (S664D) have also been described (7).…”
Section: Isolation Of Rat Liver Subcellularmentioning
confidence: 99%
“…Phosphorylation of Ser664, which is part of the basolateral sorting signal, stimulates transcytosis. Mutation of Ser-664 to Ala (S664A) reduces transcytosis, while mutation to Asp (S664D), whose negative charge may mimic a phosphate, stimulates transcytosis (7). Phosphorylation apparently works by weakening the basolateral signal, since the S664D mutant exhibits decreased TGN to basolateral sorting, increased TGN to apical sorting (5), as well as decreased recycling and increased transcytosis after endocytosis.…”
mentioning
confidence: 99%
“…Adaptors interact with a tyrosine or a dileucine motif (Schmid, 1997;Kirchhausen et al, 1997;Bonifacino and Dell'Angelica, 1999). The recognition of cargo molecules can be regulated by the phosphorylation of sites close to the sorting domains; for example, in the trafficking of furin (Wan et al, 1998;Teuchert et al, 1999;Molloy et al, 1999), CD4 (Pitcher et al, 1999), CTLA-4 (Shiratori et al, 1997), MHC-II-Ii complex (Anderson and Roche, 1998), and pIgAR (Casanova et al, 1990;Okamoto et al, 1994;Luton et al, 1998). The cargo molecules are recruited into a newly forming carrier vesicle by cytoplasmic coat molecules (Matsuoka et al, 1998;Bremser et al, 1999).…”
Section: Introductionmentioning
confidence: 99%